The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3989/gya.042909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural antioxidants on the stability of ostrich meat during storage

Abstract: Meat from the ostrich is becoming increasingly popular throughout the world. The aim of the current study was to evaluate the effects of different antioxidants such as ascorbic acid (AA), α-tocopherol (Toc) and rosemary herb (Ros) on the stability of ostrich meat during storage. The chemical composition of ostrich meat showed low fat content (1.5 %) combined with high protein content (22.4 %). The combination of AA + Ros, Toc + Ros and AA + Toc was more effective in reducing the thiobarbituric acid (TBA) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In both types of meats, the level of TAB load was low with respect to all treatments. Our results are in agreement with the findings of Abou-Arab and Abu-Salem [31] who reported that TAB of ostrich meat increased with the storage intervals. Similar research was conducted on chicken meat wherechicken meat was fried and then irradiated with gamma rays.…”
Section: Total Aerobic Bacteria (Tab)supporting
confidence: 93%
“…In both types of meats, the level of TAB load was low with respect to all treatments. Our results are in agreement with the findings of Abou-Arab and Abu-Salem [31] who reported that TAB of ostrich meat increased with the storage intervals. Similar research was conducted on chicken meat wherechicken meat was fried and then irradiated with gamma rays.…”
Section: Total Aerobic Bacteria (Tab)supporting
confidence: 93%
“…Literature reports that the optimal age to slaughter ostriches is when they are between 10 and 16 months old, inclusively (Abou-Arab and Abu-Salem, 2010). The carcass weight was found to amount up to 58.6% of the total weight.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme can efficiently degrade collagen fibers found in connective tissue. Collagenase can significantly improve the quality of the product, triggering a change in protein properties (Abou-Arab and Abu-Salem, 2010). This paper presents new recipes and production technology of the two ostrich meat pates, together with an analysis of the scientific support of the food safety management system.…”
Section: Introductionmentioning
confidence: 99%